Optimizing Mixture Composition to Improve the Performance of Porous Asphalt for Wearing Course as an Environmentally Friendly Road Construction Material - Sulianti, Ika; Amiruddin, Amiruddin; Ibrahim, Ibrahim; Subrianto, A. (Jurnal Teknik Sipil dan Perencanaan, 2019)
Abstract. Porous asphalt is an alternative in flexible pavement which is considered to make water seep into the soil. In previous research have been tested the mixture ofÃ‚Â  porous asphalt that meets porous asphalt porosity requirements, but found the weaknesses that the stability is still lower than the standard required. Based on result obtained before, the study is aimed at investigating the use of mixture composition variable with different percentages until the optimal conditions were obtained, namely making a normal mixture, 15%, 18.75%, 22.5%, 26.25%, 30% as sand composition reduction. The percentage of sand reducted from previous composition with different asphalt variations. Tests are carried out using the Marshall method. Sequence of tests show that the materials used for experiment meet the requirement.Ã‚Â  Optimum Asphalt Content obtained for the mixture are 6% of the total mixed weight. The best Marshall characteristics for AC-WC porous asphalt obtained are at the percentage of 26.25% sand reduction.Ã‚Â Ã‚Â